Rational design of antibodies and development of a novel method for (1–3)-β-D glucan detection as an alternative to Limulus amebocyte lysate assay - Liu, Chunlong; Zhang, Lin; Zhang, Jiaxing; Wang, Mengfan; You, Shengping; Su, Rongxin; Qi, Wei (Frontiers in Cellular and Infection Microbiology, 2024)
With advances in medicine, increasing medical interventions have increased the risk of invasive fungal disease development. (1-3)-β-D glucan (BDG) is a common fungal biomarker in serological tests. However, Limulus resources for detecting it are scarce and difficult to breed. Therefore, finding an alternative to Limulus amebocyte lysate is essential. In this study, a new method based on chemiluminescence for detecting BDG has been established, which could shorten the sample-toresult time to around 30 min. In addition, the new method could rescue Limulus from being endangered and save much effort on equipment as well as skilled technician. An optimal V52 H I/N34 L Y mutant antibody, which has increased 3.7-fold of the testing efficiency compare to the wild-type antibody, was first achieved by mutating "hot-spot" residues of that contribute to strong non-covalent bonds, as determined by alanine scanning and molecular dynamics simulation.The mutant was then applied to develop the magnetic particle chemiluminescence method and 574 clinical samples were tested. 95 pg/ml by Limulus amebocyte lysate was used as the cut-off value to plot the receiver-operating characteristic curve. The area under the curve was 0.905 (95% CI: 0.880-0.929) and the chemiluminescence detected an antigen concentration of 89.98 pg/ml. The sensitivity and specificity were 83.33% and 89.76%, respectively. In conclusion, the results of chemiluminescence showed a good agreement with Limulus amebocyte lysate. The study demonstrates the feasibility of using BDG mutant antibodies for invasive fungal disease diagnosis.